Advances in the development of a biofungicide: Physical-chemical characterization and antifungal activity of propolis - Cibanal, Irene Laura; Fernández, Leticia A.; Krepper, Gabriela; Pellegrini, Cecilia Noemí; Gallez, Liliana María (Agrociencia Uruguay, 2019)
Propolis is a viable alternative for chemical control of plant pathogens due to its antimicrobial properties. The present study was conducted to determine the sensorial, physical and chemical characteristics of four propolis from Argentina, and their respective hydroalcoholic extracts. In vitro antifungal activity of hydroalcoholic propolis extracts against Penicillium sp. that cause the decay of garlic (Allium sativum) was also studied. All propolis samples were composed of irregular fragments. The aroma was mainly resinous. The predominant colour was brown. The analysis of the raw samples showed differences in the parameters wax content (9.43-31.16 %), loss by heating (1.04-1.46 %), ashes (0.98-7.1 8 %) and melting point (63.16-67.5 °C). The hydroalcoholic extracts of propolis also differ in the dry residue (5.50-9.30 %), content of phenols (23.44-53.91 mg eq galic/g propolis), total flavonoids (11.23-15.88 mg eq quercetin/g propolis) and oxidation index (2.25-4.33 seconds). The evaluation of the antifungal activity demonstrated that all the treatments containing propolis had an inhibitory effect over 99 % on fungi colony-forming units’ development. Although the physical and chemical study showed significant differences between propolis samples, all exhibited excellent antifungal activity against Penicillium sp. This demonstrates the potential of different propolis for the development of a biofungicide for agricultural use.